2022
DOI: 10.3390/ijms231911661
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ABC Transporter G Subfamily in Pomegranate and Function Analysis of PgrABCG14

Abstract: ATP-binding cassette subfamily G (ABCG) proteins play important roles in plant growth and development by transporting metabolites across cell membranes. To date, the genetic characteristics and potential functions of pomegranate ABCG proteins (PgrABCGs) have remained largely unknown. In this study, we found that 47 PgrABCGs were divided into five groups according to a phylogenetic analysis; groups I, II, III, and IV members are half-size proteins, and group V members are full-size proteins. PgrABCG14, PgrABCG2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…In our study, most PgCAD gene structures in group II were consistent with pattern I, the PgCAD gene structure of group I (PgCAD7, PgCAD18) was consistent with pattern II, the members of groups III and IV were consistent with pattern III, and PgCAD10 and PgCAD13 did not fall into any of these three modes. Similar findings were found for CAD genes in other species [28,39].…”
Section: The Gene Structures and Protein Domains Analysis Of The Cad ...supporting
confidence: 88%
See 1 more Smart Citation
“…In our study, most PgCAD gene structures in group II were consistent with pattern I, the PgCAD gene structure of group I (PgCAD7, PgCAD18) was consistent with pattern II, the members of groups III and IV were consistent with pattern III, and PgCAD10 and PgCAD13 did not fall into any of these three modes. Similar findings were found for CAD genes in other species [28,39].…”
Section: The Gene Structures and Protein Domains Analysis Of The Cad ...supporting
confidence: 88%
“…The seed hardness of pomegranate is positively correlated with the lignin content. Reducing the lignin content can significantly reduce the seed hardness [39]. CAD catalyzes the last step of lignin synthesis and is an important indicator of lignin content.…”
Section: Discussionmentioning
confidence: 99%
“…A similar increase in gene copy number is also found in the downstream ABC transporter family ( Pc : 54, Sa : 187, Pe : 318, Ss : 299) (Miao & Liu, 2010). In both polyploidies, we detected about three times ( Pe : 30, Ss :31, Sa : 28, Pc :10) increase of the gene copy number in this subfamily‐G of ABC family which was reported to participate in the monomers transport in suberin lamellae development and lignin accumulation (Yadav et al., 2014; Yu et al., 2022). Over 90% of these genes exhibit expression in either the leaves or stems.…”
Section: Resultsmentioning
confidence: 83%
“…For example, de Lima et al found that the ABC gene (Sv-ABCG17) is a potential transporter of lignin monomers [25]. Yu et al suggested the potential role of the ABC gene (PgrABCG14) in promoting plant growth and lignin accumulation [26]. Xie et al identified ABC family genes in Phanerochaete chryso-sporium and suggested that the transporter protein identified in the P. chrysosporium secretomes could play a role in cellobiose and/or cellodextrin uptake [27].…”
Section: Introductionmentioning
confidence: 99%